Adjuvant Chemotherapy for Stage III Colon Cancer - Taieb, Julien (Cancers (Basel), 2020)
SIMPLE SUMMARY: In patients with stage III colon cancer, adjuvant chemotherapy with a fluoropyrimidine combined with oxaliplatin reduces the risk of recurrence and mortality, with a treatment duration that may be shortened from 6 to 3 months in certain situations allowing to limit toxicities, especially cumulative sensitive neuropathy. However, it is difficult to effectively predict the risk of recurrence individually for each patient. It is indeed necessary not to over-treat patients with potential toxicities of chemotherapy and, conversely, not to under-treat patients at high risk of recurrence, and also to find new treatment approaches for specific subgroups. Though no single biomarker have sufficient predictive value to adapt the therapeutic strategy, we have considerably improved our knowledge of these biomarkers predictive of recurrence in localized colon cancer and many trials testing their ability to guide treatment are ongoing. ABSTRACT: In patients with stage III colon cancer (CC), adjuvant chemotherapy with the combination of oxapliplatin to a fluoropyrimidine (FOLFOX or CAPOX) is a standard of care. The duration of treatment can be reduced from 6 months to 3 months, depending on the regimen, for patients at low risk of recurrence, without loss of effectiveness and allowing a significant reduction in the risk of cumulative sensitive neuropathy. However, our capacity to identify patients that do really need this doublet adjuvant treatment remains limited. In fact, only 30% at the most will actually benefit from this adjuvant treatment, 50% of them being already cured by the surgery and 20% of them experiencing disease recurrence despite the adjuvant treatment. Thus, it is necessary to be able to better predict individually for each patient the risk of recurrence and the need for adjuvant chemotherapy together with the need of new treatment approaches for specific subgroups. Many biomarkers have been described with their own prognostic weight, without leading to any change in clinical practices for now. In this review, we will first discuss the recommendations for adjuvant chemotherapy, and then the different biomarkers described and the future perspectives for the management of stage III CC.